Comparison of clinical efficacy of robot-assisted and freehand core decompression in the treatment of osteonecrosis of the femoral head: a systematic review and meta-analysis - Ouyang, Wensi; Guo, Guimei; Jiang, Tianpei; Zhao, Changwei; Zhou, Xiaoling (BMC musculoskeletal disorders, 2024)
Objective At present, the core decompression (CD) has become the main surgical procedure for the treatment of osteonecrosis of the femoral head (ONFH); however, the CD surgery requires high operator experience and repeated fluoroscopy increases the radiation damage to patients, and medical staff. This article compares the clinical efficacy of robot-assisted and freehand CD for ONFH by meta-analysis. Methods Computer searches of PubMed, Web of Science, Embase, Cochrane Library, Chinese National Knowledge Infrastructure, China Science and Technology Journal Database, WanFang, and Chinese BioMedical Literature Database were conducted from the time of database inception to November 15, 2023. The literature on the clinical efficacy of robot-assisted and freehand CD in the treatment of ONFH was collected. Two researchers independently screened the literature according to the inclusion and exclusion criteria, extracted data, and strictly evaluated the quality of the included literature. Outcome measures encompassed operative duration, intraoperative blood loss volume, frequency of intraoperative fluoroscopies, visual analog scale (VAS) score, Harris hip score (HHS), complications, and radiographic progression. Data synthesis was carried out using Review Manager 5.4.1 software. The quality of evidence was evaluated according to Grades of Recommendation Assessment Development and Evaluation (GRADE) standards. Results Seven retrospective cohort studies involving 355 patients were included in the study. The results of meta-analysis showed that in the robot-assisted group, the operative duration (MD = -17.60, 95% CI: -23.41 to -11.78, P < 0.001), intraoperative blood loss volume (MD = -19.98, 95% CI: -28.84 to -11.11, P < 0.001), frequency of intraoperative fluoroscopies (MD = -6.60, 95% CI: -9.01 to -4.20, P < 0.001), and ΔVAS score (MD = -0.45, 95% CI: -0.67 to -0.22, P < 0.001) were significantly better than those in the freehand group. The GRADE evidence evaluation showed Δ VAS score as low quality and other indicators as very low quality. There was no significant difference in the terms of ΔHHS (MD = 0.51, 95% CI: -1.34 to 2.35, P = 0.59), complications (RR = 0.30, 95% CI: 0.03 to 2.74, P = 0.29), and radiographic progression (RR = 0.50, 95% CI: 0.25 to 1.02, P = 0.06) between the two groups. Conclusion There is limited evidence showing the benefit of robot-assisted therapy for treatment of ONFH patients, and much of it is of low quality. Therefore, caution should be exercised in interpreting these results. It is recommended that more high-quality studies be conducted to validate these findings in future studies. Systematic review registration https://www.crd.york.ac.uk/prospero/ #recordDetails, CRD42023420593.